Influence of vasostatins, the chromogranin A-derived peptides, on the working heart of the eel (Anguilla anguilla): negative inotropy and mechanism of action - Imbrogno S; Angelone T; Adamo C; Helle KB; Tota B.; CORTI , ANGELO (General and Comparative Endocrinology, 2004)
We have studied the effects of exogenous human recombinant Vasostatin-1 (VS-1), Vasostatin-2 (VS-2) and the human Chromogranin A (CGA) 7-57 synthetic peptides on the mechanical performance of the isolated and perfused working eel (Anguilla anguilla) heart. Under basal conditions, the three peptides decreased stroke volume (SV) and stroke work (SW), thus exerting negative inotropism. The VS-1-mediated negative inotropism was abolished by exposure to inhibitors of either Gi/o protein (pertussis toxin; PTx) or M1 muscarinic receptors (Pirenzepine) or calcium (Lantanum and Diltiazem) and potassium (Ba2+, 4-aminopyridine, tetraethylammonium, glibenclamide) channels, while it required an intact endocardial endothelium (EE). Using N-G-monomethyl-L-arginine (L-NMMA) as an inhibitor of nitric oxide (NO) synthase (NOS), and hemoglobin as a NO scavenger, we demonstrated the obligatory role of NO signaling in mediating the vasostatin response. Pretreatment with either a specific inhibitor of soluble guanylate cyclase (GC) 1H-(1,2,4)oxadiazolo-(4,3-alpha)quinoxalin-1-one (ODQ) or the inhibitor of the cGMP-activated protein kinase (PKG) KT5823, abolished the VS-1-mediated inotropism, indicating the cGMP-PKG component as a crucial target of NO signaling. Of note, VS-1 was effective in counteracting the adrenergic (Isoproterenol and Phenylephrine)-mediated positive inotropism. These findings provide the first evidence that vasostatins exert cardiotropic action in fish, thus suggesting their long evolutionary history as well as their species-specific mechanisms of action. (C) 2004 Elsevier Inc. All rights reserved.